Abnormal Spontaneous Eye Movements as Initial Presentation of Organophosphate Poisoning. (7th February 2017) - De Lima Teixeira, Igor; Bazan, Silméia Garcia Zanati; Schelp, Arthur Oscar; Luvizutto, Gustavo José; De Lima, Fabrício Diniz; Bazan, Rodrigo
Background: Atypical ocular bobbing may result from an intentional poisoning from an organophosphate compound. Phenomenology Shown: The patient exhibited conjugated, slow, arrhythmic, unpredictable eye movements in all directions, diagnosed as atypical ocular bobbing. Educational Value: This is a rare, well‐documented, clinically relevant case for medical students for correct diagnosis and appropriate treatment of organophosphate intoxication.